2020
DOI: 10.3390/wevj12010002
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Electric Vehicle Charging Stations in Thailand: Policies, Players, and Key Issues (2015–2020)

Abstract: This article explored the development of electric vehicle (EV) charging stations in Thailand between 2015 and 2020. This research aimed to study the main players and examine their goals, strategies, and operations in the EV charging business as well as the key issues that these charging operators have encountered in developing charging stations. The authors collected qualitative data (direct interviews with managers, video interviews, news, research articles, industry reports and press releases of EV charging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…An analysis of the array of publications, where along with the opinions of experts were the opinions of drivers, showed that ordinary drivers are interested in getting to know this type of transport better but in the presence of a regulated service network and developed infrastructure of gas stations and service stations. The same facts in the social, economic, investment, and technical interpretation are confirmed in several foreign scientific works [16][17][18][19][20][21].…”
Section: Introductionsupporting
confidence: 61%
“…An analysis of the array of publications, where along with the opinions of experts were the opinions of drivers, showed that ordinary drivers are interested in getting to know this type of transport better but in the presence of a regulated service network and developed infrastructure of gas stations and service stations. The same facts in the social, economic, investment, and technical interpretation are confirmed in several foreign scientific works [16][17][18][19][20][21].…”
Section: Introductionsupporting
confidence: 61%
“…Te research and development of chargers have become a key technical problem in solving electric vehicle charging, in order to realize convenient and timely charging of power batteries anytime, anywhere, and enhance the public's interest and confdence in using electric vehicles [6]. Power factor correction technology is a very important part of the onboard charging system, which is a necessary device to meet the green environmental protection requirements of power electronic products, and is a key technology in the development of onboard chargers in the future [7].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of physical RFID cards has added a complication [133] despite the research in this study of chargers' availability. Different manufacturers started to use their cards, so an electromobility development journey required several cards [134], for example, one for own home stations and another with access to a particular operator. The various cards for several operators are currently being leveled by providing the possibility of controlling one's own card, which is programmed for several separate companies [135].…”
Section: Discussionmentioning
confidence: 99%